2021
DOI: 10.1038/s41467-021-23593-z
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of microRNA expression via E2F1 downregulation promotes Salmonella infection both in infected and bystander cells

Abstract: Cells infected with pathogens can contribute to clearing infections by releasing signals that instruct neighbouring cells to mount a pro-inflammatory cytokine response, or by other mechanisms that reduce bystander cells’ susceptibility to infection. Here, we show the opposite effect: epithelial cells infected with Salmonella Typhimurium secrete host factors that facilitate the infection of bystander cells. We find that the endoplasmic reticulum stress response is activated in both infected and bystander cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…Along this line, we validated that the expression of mature miR-183 and its precursor pri-miR-183 was indeed regulated by E2F1. This is in line with recent miRNA sequencing data demonstrating a 60% decrease in expression of miR-183-5p upon knockdown of E2F1 in HeLa cells [ 58 ]. Of note, the oncogenic miRNAs miR-182 and miR-96 originating from the same primary transcript as miR-183 are coordinately downregulated by knockdown of E2F1 in this dataset.…”
Section: Resultssupporting
confidence: 91%
“…Along this line, we validated that the expression of mature miR-183 and its precursor pri-miR-183 was indeed regulated by E2F1. This is in line with recent miRNA sequencing data demonstrating a 60% decrease in expression of miR-183-5p upon knockdown of E2F1 in HeLa cells [ 58 ]. Of note, the oncogenic miRNAs miR-182 and miR-96 originating from the same primary transcript as miR-183 are coordinately downregulated by knockdown of E2F1 in this dataset.…”
Section: Resultssupporting
confidence: 91%
“…Cross-talk between infected and uninfected neighbouring cells has previously been described for many bacterial or viral pathogens, for example through cytokines signalling (Milivojevic et al, 2017;Bost et al, 2020), or directly through uptake of pathogen effector proteins from infected to uninfected cells (Guidi et al, 2013). S. Typhimurium was also shown to cause a reprogramming of microRNAs in infected cells, affecting also bystander cells (Aguilar et al, 2021). Endoplasmic reticulum stress response is activated in bystander cells, affecting many genes' expression; in particular downregulating key transcription factors, such as E2F1.…”
Section: Discussionmentioning
confidence: 95%
“…S . Typhimurium was also shown to cause a reprogramming of microRNAs in infected cells, affecting also bystander cells ( Aguilar et al., 2021 ). Endoplasmic reticulum stress response is activated in bystander cells, affecting many genes’ expression; in particular downregulating key transcription factors, such as E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, let-7i-3p is downregulated in porcine ileum, and has been shown to control Salmonella adhesion and intracellular replication [ 8 ]; also, miR-15a-5p, miR-15b-5p, miR-22, miR-16-5p, miR-421, miR-744 and let-7i-5p (E2F1-dependent miRNAs) were downregulated in S . Typhimurium infected porcine ileum and colon, promoting bacterial replication [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microRNAs (miRNAs), which are conserved small non-coding post-transcriptional regulators of gene expression [ 5 ], modulate the development and function of immune cells and can have pro- or anti-inflammatory effects during bacterial infections [ 6 , 7 ]. The regulation of the transcriptional response by miRNAs in Salmonella infection is still mostly unclear, but several miRNAs such as let-7i or miR-15 have been shown to modulate certain host immune functions [ 8 , 9 ]. In a previous study, we described the transcriptomic response in the porcine ileum 2 days after infection with S .…”
Section: Introductionmentioning
confidence: 99%